Images of Bad Government: “proud Spaniards and Indian whores” in Guaman Poma de Ayala’s works - Velázquez Castro, Marcel (2020)
In the “Good Government”, the second part of his chronicle, Guaman Poma presents some of the most detailed and vivid descriptions of colonial power in the Andes. This essay looks at such descriptions from two points of view: (i) the great gap between what should have been (good behavior) and the frequent social action of authorities related to this, and (ii) the condemnation of violence against the Indians, violence manifested in physicial punishment, theft, labor abuses, rape, verbal threats, among others. The author refers to two vices to explain violence as a consequence of colonial power: greed and lust. Departing from the social problems that Guaman Poma reveals in his chronicle, this essay pays attention to the representation of the Indian body as a place for the execution of colonial power and the ambivalent role of sexuality.